Medical clerkship in a state registration and reception center for forced migrants in Germany: students’ experiences, teachable moments, and psychological burden - Kindermann, David; Schmid, Carolin; Derreza-Greeven, Cassandra; Junne, Florian; Friederich, Hans-Christoph; Nikendei, Christoph (International journal of environmental research and public health, 2019)
Aspects of global health are becoming increasingly relevant for doctors of future generations. However, medical curricula rarely include courses which focus on global health or forced migration. Furthermore, it remains unclear whether students are at risk to develop psychological strain, after being confronted with highly burdened or even traumatized asylum seekers. This is a prospective study using a mixed-methods approach. We included n = 22 medical students performing a medical clerkship in a state registration and reception center for refugees. By applying (1) qualitative interviews, (2) reflective diaries, and (3) psychometric questionnaires, we examined the students’ experiences, teachable moments, and potential psychological burdens. In the interviews, the students emphasized the importance of cultural sensitivity during their clerkship. However, they also reported cognitive changes concerning their views of themselves and the world in general; this could indicate vicarious traumatization. The reflective diaries displayed high learning achievements. According to the psychometric questionnaires, the assignment in the reception center had not caused any significant psychological strain for the students. By completing their medical clerkship in a reception center, students were able to improve their medical, organizational, and interactional knowledge and skills. Furthermore, they reported that they had broadened their personal and cultural horizons.
Gesehen am 16.10.2019